Analisis Faktor-Faktor Yang Mempengaruhi Implementasi Kebijakan Penanganan Corona Virus Disease 19 Di Kabupaten Gowa - Muh Zulkarnain; Rabina Yunus; Andi Lukman (Jurnal Sosio Sains, 2022)
Corona Virus Disease (COVID 19) is an infectious disease caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The disease was first identified in December 2019 in Wuhan, the capital of China's Hubei province, and has since spread globally, resulting in the ongoing 2019 coronavirus pandemic. The Gowa Regency Government since the discovery of the first case of Covid 19 in Indonesia has made various innovations in handling Covid 19 in Gowa Regency. The research method is descriptive qualitative. Respondents of this study consisted of elements of policy makers, namely the Regional Secretariat and DPRD of Gowa Regency, elements of policy implementers, namely the District and District Task Force Units, and the policy target, namely the people of Gowa Regency. The results of this study can be concluded that the Gowa Regency Government is very concerned about the handling of Covid-19 marked by the existence of a legal basis in the application of Health Protocols through Regional Regulation No. 2 of 2020. However, there are still obstacles in its implementation, namely regulations related to Health Protocols and Vaccinations that inconsistent, causing controversy in the community, the application of less strict sanctions from policy implementers in accordance with the Perda no. 2 of 2020, the resources of the medical team in Gowa Regency are still lacking compared to the Coordinating Minister for People's Welfare Decree No. 54 of 2013, there were irresponsible news (hoaxes) circulating on social media that affected public confidence in Covid-19, as well as the lack of example from several local government elements in implementing health protocols. Corona Virus Disease (COVID 19) adalah penyakit menular yang disebabkan oleh sindrom pernapasan akut coronavirus 2 (SARS-CoV-2). Penyakit ini pertama kali diidentifikasi pada Desember 2019 di Wuhan, ibu kota provinsi Hubei China, dan sejak itu menyebar secara global, mengakibatkan pandemi coronavirus 2019 yang sedang berlangsung. Pemerintah Kabupaten Gowa sejak ditemukannya kasus pertama Covid 19 di Indonesia telah melakukan berbagai inovasi dalam penanganan Covid 19 di Kabupaten Gowa. Metode penelitian adalah deduktif kualitatif. Responden penelitian ini yaitu terdiri dari unsur pembuat kebijakan yaitu Sekretariat Daerah dan DPRD Kabupaten Gowa, unsur pelaksana kebijakan yaitu Satuan Gugus Tugas Kabupaten dan Kecamatan, dan sasaran kebijakan yaitu masyarakat Kabupaten Gowa. Hasil penelitian ini dapat disimpulkan bahwa Pemerintah Daerah Kabupaten Gowa sangat concern terhadap penanganan Covid-19 ditandai dengan adanya landasan hukum dalam Penerapan Protokol Kesehatan melalui Perda No 2 Tahun 2020. Akan tetapi masih terdapat kendala-kendala dalam pelaksanaannya yaitu aturan terkait Protokol Kesehatan dan Vaksinasi yang tidak konsisten sehingga menimbulkan kontroversi di masyarakat, penerapan sanksi yang kurang tegas dari pelaksana kebijakan sesuai yang tertuang dalam Perda No. 2 Tahun 2020, sumber daya tim medis di Kabupaten Gowa yang masih kurang dibandingkan dengan Kepmenko Kesra No. 54 Tahun 2013, adanya berita-berita yang tidak bisa dipertanggungjawabkan (hoax) yang beredar di media sosial yang mempengaruhi kepercayaan masyarakat terhadap Covid-19, serta kurangnya keteladanan dari beberapa oknum pemerintah daerah dalam menerapkan protokol kesehatan.